Designing a professional learning community model for primary school teachers - Amoozadeh, Raheleh; Shafizadeh, Hamid; Ahmadi, Fakhredin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Professional learning community is an extensive or moderate learning process to strengthen cooperation between job-related tasks in the work environment and has a significant effect on improving the performance of human resources. This research was conducted with the aim of designing a professional learning community model for primary school teachers. Methods: A phenomenological qualitative method based on the Claizian stage analysis approach was used. The participants of the research are 26 people, including professors and faculty members of universities in the field of educational management, principals, assistant professors and successful teachers in elementary schools, and doctoral students or graduates of the field of educational management working in education, who through sampling A targeted opinion was selected. In order to collect data, in-depth interviews with research participants were used. In order to evaluate the validity, the methods of review by members, triangulation (three-way perspective) of data sources, review by colleagues and review by supervisors are used to increase the validity of the research. Also, to check the reliability, the strategies of reliability, assurance and trustworthiness, confirmation are used. or verifiability and transferability were exploited. Results: After analyzing the data, the final model of the research includes 2 major dimensions of the antecedents of teachers' professional learning community, including 4 components of educational leadership, organizational culture, collaborative learning, and organizational structure, and finally, the consequences of teachers' professional learning community, including 3 major dimensions of quality development performance, belonging to work and school, and job and professional satisfaction were depicted. Conclusion: In order to realize the professional learning community of teachers, it is necessary and necessary to pay attention to cultural elements and dimensions. The task of teachers' professional learning community is to stimulate things such as mission, vision, collective commitment and common goals, and value creativity, risk-taking, initiative and innovation, and the existence of an atmosphere based on mutual respect as an important part of teachers' professional learning community.